GISTs-- Gastrointestinal stromal tumors - Castelguidone, Elisabetta de Lutio di.; Messina, Antonella; SpringerLink (Online service). (Milano Springer, 2011)
This book aims to provide a complete overview of the diagnosis and treatment of gastrointestinal stromal tumors (GISTs). It has been conceived to be both a detailed guide for clinical practice and an updated reference for all those involved in the evaluation of GISTs imaging. The publication provides comprehensive descriptions of the full range of common imaging and nonimaging techniques used in the diagnosis and followup of GISTs. Techniques reviewed include: Conventional radiography; Endoscopy and endoscopic ultrasound; Conventional, color-Doppler and contrast-enhanced ultrasound.
Anatomic and Clinical Pathology -- Introduction -- Conventional Radiography -- Endoscopy and Endoscopic Ultrasound in the Diagnosis and Staging of GISTs -- Ultrasound, Color-Doppler Ultrasound and Contrast-enhanced Ultrasound of Primary GISTs and Liver Metastases -- Computed Tomography -- Magnetic Resonance -- Contrast-enhanced PET/CT in the Follow-up of GISTs -- Medical Treatment -- Surgical Treatment -- GIST Unit Network.
Electronic reproduction.
Keywords: Gastrointestinal Stromal Tumors; Gastrointestinal stromal tumors; Medicine; Medical radiology; Nuclear medicine; Oncology; Pathology; Information systems; Medicine & Public Health; Imaging / Radiology; Diagnostic Radiology; Electronic books